COST ANALYSIS OF SUSPENSION BRIDGE CONSTRUCTION IN KALIMANTAN BARAT PROVINCE - Yasin, Usman; Elvira, Elvira; Lusiana, Lusiana; Herwani, Herwani (Fakultas Teknik Universitas Tanjungpura, 2024)
The successful implementation of a job begins with the determination of a reliable estimation value. One of the models used in determining the estimated value of a job, using data from the cost budget plan (RAB) on work that has been carried out, is the Cost Significant Model. In this study, the data used were five suspension bridge construction jobs starting from 2018 to 2022. the data obtained from the RAB is processed into independent variables and dependent variables, which are then tested using multiple linear regression methods using the SPSS application. Based on the results of the analysis, the influential variables are X2, namely Bridge Oprit Work; X4, namely Upper Building Work (Transportation and Installation of Truss Bridges); and X5, namely Lower Building Work (Angkur Block Work, Pyilon Foundations, Wind Ties) with a total weight of 85.30%. By using the equation Y = -21,640,343,680,000 + (1,856,843,372 x X2) + (453,953,095 x X4) + (41,965,201,370 x X5), the maximum value of 62.21% and minimum value of -98.05% are obtained, so it falls into the Class 5 category. Class 5 has an accuracy value ranging from +30% to +100%, so it is estimated that it is feasible to use it to carry out the initial concept screening estimation.